Prototype of a Device to Research Ultrasound Effects on Microbiological Processes (2013)
This article describes the development of a multifunctional prototype which supplies ultrasound to a sample in a Petri dish, between 18 KHz and 30KHz frequencies, with intensities from 0.3 mW/m2 to 1.5 mW/m2. This device guarantees sample survival with a micro-incubating system, operated by a control system and temperature monitoring. In addition, the prototype detects changes regarding the microbiological process in question, with a self-based laser-nephelometry system. The user would be able to choose parameters values mentioned, for a certain experiment, and analyze output data tables, images and statistics generated by a computer application specially designed to present this data.